High Performance Damage-Resistant Seismic Resistant Structural Systems for Sustainable and Resilient City: A Review - Junhua Wang; Hua Zhao (Shock and Vibration)
This paper presents a review of high performance damage-resistant seismic resistant structural (DRSRS) systems for the sustainable and resilient city. Firstly, the motivation and the basic principle as well as methodology of the developing DRSRS system are briefly illustrated. Then, the structural detailing and the seismic behaviors of three types of existing DRSRS systems, namely, the replaceable structural element (RSE), rocking seismic resisting structural (RSRS) system, and self-centering seismic resisting structural (SCSRS) system, are summarized in detail. The theoretical and extensive experimental study results indicated that the three existing types of DRSRS system can minimize the postdamage after loading. Types of energy dissipation devices and dampers, as well as fuse sections, can largely enhance the energy dissipation capacity of the proposed structural system. Many numerical and finite element models have been proposed to analyze the dynamic and static cyclic responses of them. The residual deformation after the dynamic response is smaller compared to that following the cyclic response. Then, the current research challenges of DRSRS system are illustrated, and the new research highlights that emerged in recent years are stated. Finally, the conclusions of this paper are summarized; furthermore, the recommendations for the future studies are pointed out at the end of the paper.